Technical Assistance of the Alliance of Bioversity International and International Centre for Tropical Agriculture (CIAT) to Agricultural Productivity & Climate Resilience Enhancement Project in Tchad (TA-ProPAD): Achievements and lessons learnt - Ogou, Anani; Kagabo, Desire; Ouedraogo, Mathieu; Sogbui, Caroline Makamto; Laderach, Peter (2024)
The Alliance of Bioversity-ClAT is providing technical support to the West and Central African Council for Agricultural Research and Development (CORAF) for the integration of Climate Smart Agriculture in the implementation of the ProPAD World Bank funded project in Chad, with the aim of scaling up CSA innovations, practices, and technologies for the benefit of Chad population. This poster was produced and presented during the joint supervision mission of the donors (CORAF & Confédération Suisse). It highlights the main achievements and results obtained during the past two years; the lessons learned from the implementation of CIAT's technical assistance, and the way forward.